Export expansion an production sharing in Malaysian manufacturing - Choong, Pai Wei *; Noor Aini, K. (School of Business & Economics, Universiti Putra Malaysia, 2019)
The rapid expansion of Malaysia’s non-resource-based manufactured exports is closely related to its participation in international production networks that are largely mediated by multinational enterprises. This study examines the extent of the Malaysian manufacturing industry participating in international production sharing and the role of intermediate imports in production sharing exports. Intermediate imports are embedded in a standard gravity equation model of bilateral exports as essential complementary inputs for international production sharing. The data is based on OECD STAN database and models estimated using dynamic panel system generalized method of moment technique to account for the dynamic process of bilateral exports and endogeneity issues. The findings show evidence of non-resource-based industry’s participation in international production sharing as supported by the positive and significant impact of intermediate imports. Malaysia’s resource-based industry involves bilateral exports based on the Heckscher-Ohlin model as evidenced by the positive and significant impact of differences in relative per capita income between countries.